(untitled) (Revista Electrónica REDINE, 2018)
This document expuse ideas in sustentable development, the importance of education for sustentable development (ESD) and the contribution of the chemical education in the understanding to achieve the same. Sustainable development is development which is able to meet current needs without compromising the resources and possibilities of future generations. He is based in the interplay of social, economic and environmental factors that can improve the quality of life. Education for sustentable development is a factor key to the achievement of these objectives is now considered to chemistry as one of the sciences necessary to the advancement of society and facilitate consistent with a sustentable economic development and therefore, the chemistry teacher should be applied teaching and learning strategies for the training of students linked with sustentable development.